Antimicrobial sensitivity and resistance pattern in urinary isolates in Bhaktapur Hospital - Subedi, Bhusan Kumar; Subedi, Shova; Khadka, Sushma; Prajaprati, Amit; Mandal, Ananda Kumar; Bhatta, Surendra Prasad (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Urinary tract infections (UTIs) are the most common bacterial infections encountered in clinical practice. The emergence of antimicrobial resistance (AMR) among uropathogens complicates treatment strategies. Regional variations in AMR patterns necessitate localized studies to guide empirical treatment effectively. Bhaktapur Hospital, a key healthcare provider in the region, provides a unique opportunity to study in this regard, contributing to better management protocols. The study aims to find out the common isolates in the urine culture and their AMR pattern to the commonly prescribed antibacterial drugs.Method: The study is of descriptive design using hospital clinical and laboratory record of urine culture and sensitivity reports analysis within the period of 2080 Kartik to 2081 Ashoj (1 year). The approval for the study was taken from Bhaktapur Hospital (Ref no. 1034/082).Result: Majority of patient of urinary tract infection were of female sex, 646 (82.6%) and within the reproductive age group, 477(61%). Common urinary isolates were found E. coli 571(72.8%%), Klebsiella 135(17.2%), Staphylococcus aureus 42(5.4%), Citrobacteria 16(2%), Actinobacter 8(1%), Pseudomonas 7(0.9%) and Proteus 3(0.4%). Antimicrobial resistance was present in all types of isolates. Urinary isolates displayed resistance in higher percentage to common antimicrobial drugs used for UTIs treatment in the institution, namely: Amoxicillin, Cefepime, Cefixime, Ciprofloxacin, Ceftazidime, Ceftriaxone, Levofloxacin and Ofloxacin. Only Amikacin, Gentamicin and Imipenem displayed satisfactory activity against urinary isolates.Conclusion: This study substantiates the existence of uropathogens resistant to the commonly used antibiotics. Further studies are needed to identify the resistance pattern with the clinical scenario and explore the ways to tackle them.